Peran Work Life Balance dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan - Annisa Drajat; Nor Norisanti; Faizal Mulia Z (IPM2KPE, 2022)
The purpose of this study was to determine the role of work life balance (balance between life inside work and outside work) and non-physical work environment on employee performance in clothing industry companies. This research method is using descriptive and associative methods. The data analysis technique used is validity test, reliability test, multiple linear analysis, including coefficient of determination test, multiple correlation coefficient and hypothesis submission using simultaneous test (F test). The results showed that the coefficient of determination test (R2) Work Life Balance and Non-Physical Work Environment affected 34.9%, the remaining 65.1% was influenced by other factors outside the study. Based on the multiple correlation coefficient test, it can be seen from the R value of 0.591%. This indicates that there is a strong relationship between Work Life Balance and Non-Physical Work Environment on Employee Performance. Based on the F test, the probability value of Sig. 0.000 <0.05 which means that together the Work Life Balance and Non-Physical Work Environment. In conclusion, the variables of Work Life Balance and Non-Physical Work Environment have a positive and significant effect on the performance of employees of PT. Beautiful Global Clothing Sukabumi Regency. Keywords: Non-Physical Work Environment, Employee Performance, Work Life Balance